Triploidía en trucha arcoiris (Oncorhynchus mykiss) : posibilidades en Colombia (2004)
ABSTRACT: Colombia has a good hatchery facility for rainbow trout (Oncorhynchus mykiss) culture, which produces the 14% of the annual national production, ranking it on third place after the red tilapia hybrid (Oreochromis spp.) and the cachama blanca (Piaractus brachypomus) with 32% and 24%, respectively. At this moment, the production of these species is relevant through the traditional procedures, but it continues being insufficient to satisfy the national and international demand. To improve its production, the biotechnology, gives the best advantages in growth and management due to the sterility effect produced by the poliploidy, through the chromosome manipulation using heat shock to obtain triploid individuals. This text display the basic biological concepts and the appropriate technical elements to obtain a high percentage of triploids in these species for Colombia.